2009
DOI: 10.1016/j.febslet.2009.08.031
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 markedly extends replicative lifespan if the NAD+ salvage pathway is enhanced

Abstract: Edited by Vladimir SkulachevKeywords: Vascular smooth muscle Senescence SIRT1 NAD + salvage Nampt a b s t r a c t Sir2 mediates lifespan extension in lower eukaryotes but whether its mammalian homolog, sirtuin 1, silent mating type information regulation 2 homolog (SIRT1), is a longevity protein is controversial. We stably introduced the SIRT1 gene into human vascular smooth muscle cells (SMCs) and observed minimal extension of replicative lifespan. However, SIRT1 activity was found to be exquisitely dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 30 publications
2
62
0
1
Order By: Relevance
“…22 However, the effect of these properties on VSMCs in atherosclerosis is not known, and other studies have shown that SIRT1 promotes human VSMC proliferation by extending replicative lifespan. 23,24 We therefore examined the role of SIRT1 on DNA repair in VSMCs and consequences of its inactivation on atherosclerosis. We show that endogenous SIRT1 is reduced in human atherosclerosis, particularly in VSMCs.…”
Section: Clinical Perspective On P 396mentioning
confidence: 99%
“…22 However, the effect of these properties on VSMCs in atherosclerosis is not known, and other studies have shown that SIRT1 promotes human VSMC proliferation by extending replicative lifespan. 23,24 We therefore examined the role of SIRT1 on DNA repair in VSMCs and consequences of its inactivation on atherosclerosis. We show that endogenous SIRT1 is reduced in human atherosclerosis, particularly in VSMCs.…”
Section: Clinical Perspective On P 396mentioning
confidence: 99%
“…[55]. A similar direct relationship between Nampt, intracellular NAD levels and SIRT1 activity has been recently confirmed in several cell types including skeletal myoblasts [56], vascular smooth muscle cells [7], [57], and chondrocytes [58]. Of interest, the nuclear form of Nicotinamide…”
Section: Modulation Of Sirtuin Activity Through Nad Metabolismmentioning
confidence: 61%
“…Noteworthy, sirtuin activity has been shown to play a role in related processes such as cellular and organismal lifespan extension [6], [7], glucose homeostasis [63] and cellular differentiation [42], [58]. The work reviewed herein suggests that some of the pathological processes linked to metabolic disorders or aging may in fact be functionally linked to the immunomodulatory function of this family of metabolic sensors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sir2 (silent information regulator 2) in simple eukaryotes and its mammalian ortholog SIRT1 play important roles in life span extension in response to caloric restriction (Boily et al 2008). The efficacy of SIRT1 in enhancing the life span in mammals appears to depend on salvaging NAD in the nicotinamide phosphoribosyl transferase pathway (Ho et al 2009a). The phenolic compound resveratrol activates sirtuins and increases the life span in Saccharomyces cerevisiae, Caenorhabditis elegans, Drosophila melanogaster, and the fish Nothobranchius furzeri, but its efficacy in mammals is uncertain (Evason et al 2005;Howitz et al 2003;Kang et al 2002;Valenzano et al 2006).…”
Section: Acetylation Of Histonesmentioning
confidence: 99%